Sulfate‐Enabled Nitrate Synthesis from Nitrogen Electrooxidation on a Rhodium Electrocatalyst. Issue 26 (3rd May 2022) - Li, Tieliang; Han, Shuhe; Cheng, Chuanqi; Wang, Yuting; Du, Xiwen; Yu, Yifu; Zhang, Bin
Abstract: The electrocatalytic nitrogen oxidation reaction (NOR) to generate nitrate is gaining increasing attention as an alternative approach to the conventional industrial manufacture. But, current progress in NOR is limited by the difficulties in activation and conversion of the strong N≡N bond (941 kJ mol −1 ). Herein, we designed to utilize sulfate to enhance NOR performance over an Rh electrocatalyst. After the addition of sulfate, the inert Rh nanoparticles exhibited superior NOR performance with a nitrate yield of 168.0 μmol gcat −1  h −1 . The 15 N isotope‐labeling experiment confirmed the produced nitrate from nitrogen electrooxidation. A series of electrochemical in situ characterizations and theoretical calculation unveiled that sulfate promoted nitrogen adsorption and decreased the reaction energy barrier, and in situ formed sulfate radicals reduced the activation energy of the potential‐determining step, thus accelerating NOR. Abstract : Sulfate is demonstrated to enhance the nitrogen oxidation reaction (NOR) over an Rh electrocatalyst. A series of electrochemical in situ characterizations show that sulfate promotes nitrogen chemical adsorption and NO intermediate formation. Theoretical calculations further reveal that sulfate enhances nitrogen adsorption and reduces the reaction energy barrier and activation energy of nitrogen oxidation.